Brazilian Validation of the Attachment to God Inventory (IAD-Br) - August, Hartmut (Religions, 2018)
Bowlby's Attachment Theory proposes that the person seeks protection and security with his or her caregiver, establishing a significant bond, which Bowlby characterizes as attachment relationship. The relationship with God can also be understood as an attachment relationship. Until now, there are no instruments in Brazil to measure one's attachment to God. The purpose of this article is to present the adaptation and validation process of the Attachment to God Inventory for the Brazilian context, resulting in a Brazilian version of the Attachment to God Inventory (IAD-Br). The validation methodology for the IAD-Br consisted of Portuguese translation, reverse translation to English, pre-test, data collection, and validation through confirmatory factorial analysis (CFA). A total of 470 people participated in the study: 179 men and 291 women. Confirmatory factorial analysis presented unsatisfactory statistical parameters. Of the 28 items of the instrument, 11 items did not present adequate Item-Total Correlation. After excluding these 11 items, the instrument presented adequate adjustment indices. The IAD-Br, composed of 17 items, is able to be used to measure attachment to God in Brazil and constitutes a relevant instrument to identify the attachment to God style, being useful for application in the psychotherapeutic clinic and in contexts of spiritual care.